Lottie Moon : A Southern Baptist Missionary to China in History and Legend - Sullivan, Regina D., 1962- (Book collections on Project MUSE., 2011)
Regina Sullivan's captivating biography of Charlotte "Lottie" Moon is the first comprehensive portrait of the legendary Southern Baptist missionary. Moon, who began her mission work in China in 1885, helped inspire the creation of the Woman's Missionary Union - an auxiliary of the Southern Baptist Convention- which grew to have over one million members and become one of the most influential religious organizations in the United States